PKM. PELATIHAN PENGEMBANGAN KEMAMPUAN BERBAHASA INGGRIS DENGAN BELAJAR 'PARTS OF BODY' MELALUI METODE AUDIO VISUAL DAN AUDIO LINGUAL - Ni Komang Purwaningsih; Si Putu Agung Ayu Pertiwi Dewi (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2024)
Community service activities with the theme "Growing Mind: Show Your Smile, Blow Your Mind for Learning Our Body" is a theme raised with the aim of developing children's minds by learning happily and learning intelligently to understand body parts in English. The objectives of this PKM activity were: (1) imitating saying English words according to the picture, (2) saying English words according to the picture, (3) matching the sound of the English word with the picture that symbolizes it, and (4) connecting the picture and writing English. The method used was socialization and mentoring. Presentation of material about increase your knowledge of English by learning 'parts of the body' through audio-visual and audio-lingual methods. The participants in this activity were 36 students of SD Negeri 8 Padang Sambian Kaja. The results of this PKM activity were: (1) using an approach method through field observations, (2) the team provided facilities in the form of delivering materials, prizes, and providing consumption in the form of healthy drinks such as milk to students at SD Negeri 8 Padang Sambian Kaja, Kec. West Denpasar. (3) training through materials, games and question and answer sessions, (4) evaluation of activities regarding the understanding of counseling participants. From the results obtained, useful PKM activities was obtained related to increasing knowledge of English by learning 'parts of the body' through audio visual and lingual methods.